Two cases of osteoid osteoma in skulls dating from the 13–14th centuries from St. Elisabeth’s Church in Wrocław, Poland - Gawlikowska-Sroka, Aleksandra; Kwiatkowska, Barbara; Szczurowski, Jacek; Gronkiewicz, Stanisław; Dąbrowski, Paweł (Anthropological Review, 2016)
In the study two human skulls recovered from archaeological excavations at St. Elizabeth’s Church in Wrocław, dating from the 13-14th centuries were assessed. Direct measurements of each skull were recorded, and X-ray images in P-A, lateral and basal projections were taken. The skulls represented adult males. Large, bony, lobular tumours were found on the palatine bones of both skulls. X-ray examination identified these tumours as osteoid osteomas, which are benign bone tumours that may originate in the periosteum or may be located inside the bone, distorting the maxilla or mandible. However, osteoid osteoma of the palatine is very rare. This study extends our knowledge regarding the health and diseases of historical populations.